KUALITAS LAYANAN, PERSEPSI HARGA, DAN CITRA PERUSAHAAN TERHADAP KEUNGGULAN BERSAING TRANSPORTASI ONLINE - Anastasia (2024)
Technology is evolving and leading to new ways of buying goods or services. This innovation developed until the emergence and entry of online transportation in Indonesia. This study aims to prove and analyze the effect of service quality, price perception, and company image on competitive advantage. This research is a quantitative study with a population of online transportation users (GrabBike) who live in Jabodetabek. The sample size in this study was 96 respondents using non-probability sampling method. The data analysis technique used is the Partial Least Square (PLS) method using SmartPLS 4.0. Data collection in this study was carried out by distributing questionnaires via Google Form. The results showed that service quality has a positive and significant effect on competitive advantage with an original sample value of 0.377, price perceptions have a positive and significant effect on competitive advantage with an original sample value of 0.287, and company image has a positive and significant effect on competitive advantage with an original sample value of 0.280.